2010
DOI: 10.1007/s11218-010-9118-y
|View full text |Cite
|
Sign up to set email alerts
|

Social perceptions of achieving students and achievement goals of students in Malaysia and the Philippines

Abstract: The study investigates the hypothesis that country differences in achievement goals of students are associated with differences in how students with different achievement goals are perceived by students in different cultures. University students from Malaysia and the Philippine were asked to complete questionnaires on their achievement goals and on their perceptions of hypothetical students who exemplify the different achievement goals. The perception questions related to social goals such as peer affiliation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…This is a possible reason why the relationship between these two goals was quite high for the Filipino students. Similar positive correlations have been found in other collectivist settings such as those in China, Singapore, and Japan (Bernardo, 2008;Bernardo & Ismail, 2010;dela Rosa, 2010;dela Rosa & Bernardo, 2013;Chan & Lai, 2006;Chan, Lai, Leung, & Moore, 2005;Chang & Wong, 2008;Ho & Hau, 2008;Kim et al, 2010;Lau, Liem, & Nie, 2008;Shi et al, 2001;Tanaka, Okuno, & Yamauchi, 2002).…”
Section: Discussionsupporting
confidence: 67%
“…This is a possible reason why the relationship between these two goals was quite high for the Filipino students. Similar positive correlations have been found in other collectivist settings such as those in China, Singapore, and Japan (Bernardo, 2008;Bernardo & Ismail, 2010;dela Rosa, 2010;dela Rosa & Bernardo, 2013;Chan & Lai, 2006;Chan, Lai, Leung, & Moore, 2005;Chang & Wong, 2008;Ho & Hau, 2008;Kim et al, 2010;Lau, Liem, & Nie, 2008;Shi et al, 2001;Tanaka, Okuno, & Yamauchi, 2002).…”
Section: Discussionsupporting
confidence: 67%
“…Achievement goal theory focuses on the types of goals (purpose or reasons) (Ames, 1992;Pintrich, 2000) that dictate achievement-related behaviours. However, students in higher education hold low achievement goals (Bernardo & Ismail, 2010;Chen, 2015) to avoid challenges (Pulkka & Niemivirta, 2015). Prior research also found that such students tend to engage in task-avoidance (David, 2012;Gillet, Lafrenière, Huyghebaert, & Fouquereau, 2015;Stoeber, Haskew, & Scott, 2015) and self-avoidance goals (Stoeber et al, 2015) compared to task and self-approach goals.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, social‐oriented achievement motive is considered an approach‐based motivation, and as such, is likely to lead students to adopt approach‐based goals. Indeed, studies have demonstrated the presence of social reasons in the construction of approach‐based achievement goals (Bernardo, 2008; Bernardo & Ismail, 2010; Chang & Wong, 2008; Tao & Hong, 2000; Urdan & Mestas, 2006). Bernardo, for example, argued that the similar effects of performance‐approach and mastery‐approach goals on achievement found with Filipino students seemed to be attributable to a similar reason, that is, an intention to fulfill moral obligations and parental expectations.…”
mentioning
confidence: 99%